2004
DOI: 10.1097/01.pcc.0000112373.71645.2a
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age effects on outcome after pediatric traumatic brain injury*

Abstract: There is evidence from this large study that girls do not have a better outcome after pediatric traumatic brain injury than boys, with a suggestion that girls may do worse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 60 publications
3
40
2
2
Order By: Relevance
“…A study for risk factors for stroke among children with sickle cell disease found no effect of sex on stroke prevalence, 26 nor was there an effect of gender on mortality after pediatric traumatic brain injury. 27 However, after pediatric traumatic brain injury, girls demonstrate a significantly better outcome in tests of learning and memory. 28 -29 In experimental animal models, reduced sensitivity to ischemic injury in females has been attributed to circulating estradiol, a factor not relevant to prepubertal animals.…”
Section: Sex and Perinatal Injurymentioning
confidence: 99%
“…A study for risk factors for stroke among children with sickle cell disease found no effect of sex on stroke prevalence, 26 nor was there an effect of gender on mortality after pediatric traumatic brain injury. 27 However, after pediatric traumatic brain injury, girls demonstrate a significantly better outcome in tests of learning and memory. 28 -29 In experimental animal models, reduced sensitivity to ischemic injury in females has been attributed to circulating estradiol, a factor not relevant to prepubertal animals.…”
Section: Sex and Perinatal Injurymentioning
confidence: 99%
“…Our findings warrant further study into the role age-specific mechanisms of TBI pathophysiology may have in mediating this association. [30][31][32][33][34] Sex Although several researchers [35][36][37][38][39] have suggested neuroprotection for females after TBI, other studies [40][41][42] suggest poorer outcomes for females after TBI. Additionally, high school and collegiate female athletes have a higher incidence of concussion than their male counterparts 3,43 and may be at greater risk for postconcussive syndrome after mild TBI.…”
Section: Agementioning
confidence: 99%
“…Controlled experiments in animals have shown improved survival and cognitive function among females after TBI compared to males (Bramlett and Dietrich, 2001;O'Connor et al, 2003;Wagner et al, 2004), suggesting that female sex is somehow neuroprotective. However, multiple observational studies in humans have reported poorer outcomes among females after both severe TBI (Cifu et al, 1997;Donders and Woodward, 2003;Edna and Cappelen, 1987;Kaplan and Corrigan, 1992;Kirkness et al, 2004;Kraus et al, 2000;Levin et al, 1987;McMordie et al, 1990;Morrison et al, 2004;Wilberger et al, 1991), and mTBI (Bazarian and Atabaki, 2001;Bazarian et al, 1999;Jensen and Nielsen, 1990;Rutherford et al, 1977Rutherford et al, , 1979.…”
mentioning
confidence: 99%